Brokered boundaries : creating immigrant identity in anti-immigrant times - Massey, Douglas S. (Russell Sage Foundation, 2010)
"A compelling and sobering account of the lives of immigrants in a time of economic downturn and harsh anti-immigrant policies. Based on interviews with first- and second-generation, mostly undocumented, Latinos in the urban northeast, Brokered Boundaries shows how they develop a new sense of themselves and American society in the face of exclusionary barriers. Anyone wanting to understand how immigrants are navigating life in the United States today should read this important, well-written, and thought-provoking book."--Nancy Foner, Distinguished Professor of Sociology, Hunter College and Graduate Center of the City University of New York